Survey and Risk Assessment of Contaminants in Soil from a Nitrogenous Fertilizer Plant Located in North China - Xizhao Tian; Cunliang Fan; Zhiqiang Gong; Ziting Yuan; Zhiyuan Ma; Xiaosen Xing; Wei He; Pengfei Jin (Journal of Chemistry)
China is the world’s largest consumer of fertilizer, with fertilizer plants widely distributed throughout the country. With the removal and closing of fertilizer factories in recent years, pollutant surveys and risk assessments (human health risks) for these sites have become increasingly necessary. However, there has been little research on contaminated fertilizer factory sites. This study aimed to characterize the distribution of pollutants, assess the health risk of the site, and calculate the remediation area and volume in a typical fertilizer plant site in North China. A total of 443 samples were collected in 2019; they indicated that the study site had high concentrations of copper (Cu), ammonia-nitrogen (NH3-N), total petroleum hydrocarbons (TPH), and fluoride at maximum ratios (the ratio of the highest value of all test data for a particular pollutant to the standard value of the pollutant) of 3.30, 2.55, 19.69, and 1.10, respectively. The health risk assessment results suggested that some hazard quotients exceeded the threshold safe level (>1 established by environmental regulations). The risk control values of soil were 2000 mg/g (Cu), 826 mg/g (TPH), and 1549 mg/g (NH3-N), and the total remediation soil volume was 72860.71 m3. The results provided basic information on soil pollution control and environmental management in a contaminated fertilizer plant site.